Analysis of Spatial Diversification of Economic Growth Level in Powiats of Dolnośląskie Voivodship - Chądzyńska, Elżbieta (Comparative Economic Research. Central and Eastern Europe, 2013)
Intensive economic and urban processes which take place in Polish urbanized area have a significant impact on the changes of structure of territorial units, their functional development and demographic processes. Development of individual units is dependent on many factors like the location, demographic potential and economics. In the area of one voivodship – there are powiats with a various potential of development. As a subject of research powiats in the area of the Dolnośląskie Voivodship are selected. Taxonomic methods were used for the classification and grouping of powiats as a spatial objects tested in the multidimensional space of characteristics. The aim of the paper is to present the spatial variation in the level of development in the light of selected factors.